Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1902/jop.2006.p04039
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Evaluation of Loss of Attachment in HIV‐Infected Women Compared to HIV‐Uninfected Women

Abstract: CD4 count and viral load had no consistent effects on PD or AL. Among HIV-infected women, a 10-fold increase in viral load was associated with a marginal increase in tooth loss. The progression of periodontal disease measured by PD and AL did not significantly differ between HIV-infected and HIV-uninfected women. The HIV-seropositive women lost more teeth. Race, smoking, drug use, income, and education level did not influence the results for either group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
3
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 28 publications
(34 reference statements)
7
59
3
2
Order By: Relevance
“…It seems that oriented self care is the key point in the maintenance of oral hygiene in HIV infected subjects. These results are in agreement with those of other authors, who have achieved success after mechanical therapy in HIV infected patients (2,7,11,12 In this study, the supportive periodontal therapy and the patient's cooperation in maintenance of oral hygiene improved the periodontal aspect in both HIV-seropositive and AIDS patients. There are some limitations which must be considered before the conclusions are drawn because this study was conducted in a closed population, represents a small sample and the non inclusion of a control group due to ethnical concepts by asking for HIV tests.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It seems that oriented self care is the key point in the maintenance of oral hygiene in HIV infected subjects. These results are in agreement with those of other authors, who have achieved success after mechanical therapy in HIV infected patients (2,7,11,12 In this study, the supportive periodontal therapy and the patient's cooperation in maintenance of oral hygiene improved the periodontal aspect in both HIV-seropositive and AIDS patients. There are some limitations which must be considered before the conclusions are drawn because this study was conducted in a closed population, represents a small sample and the non inclusion of a control group due to ethnical concepts by asking for HIV tests.…”
Section: Discussionsupporting
confidence: 93%
“…These results suggest that immunodeficiency alone does not predispose patients to gingival and periodontal disease, since patients underwent an oral hygiene protocol. Other authors have also reported no consistent effect between periodontal status, HIV infection and CD4 count (3,4,7,11,20). A clear reduction in the gingival parameters and the improvement in the gingival condition in different HIV staging groups were evident after mechanical therapy.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, the occurrence of enterobacteria was high in HIV-patients with necrotizing periodontitis and displaying CD 4 + < 200/mm 3 . The role of the superinfecting microorganisms in patients with necrotizing periodontitis, remains unclear.…”
Section: Discussionmentioning
confidence: 53%
“…Clinical characteristics of periodontal disease in HIV-patients are closely related to the immunological status. Hence, in symptomatic HIV-patients, whose CD4+ cell counts are below 200/mm 3 in the blood, necrotizing and acute involvements of the periodontal tissues are common, frequently followed by intense malodor, bleeding and pain (15), besides a rapid loss of attachment (3).…”
Section: Introductionmentioning
confidence: 99%